Some topical legal issues of the taxation in the field of subsoil in the Republic of Kazakhstan - Shakhiyeva, A.M. (World Applied Sciences Journal Vol 26 No 8, 1061-1063, 2013)
This article examines the legal issues of the tax treatment provided by the state to the subsoil users within last 20 years
Keywords: Preferences; Retroactive tax law and tax law; Tax regime; Taxation in subsoil use area